Thought Partner. - Ciampaglia, Dante A. (Architectural Record, 2025)
The article focuses on the integration of artificial intelligence (AI) into the architecture profession, highlighting its role in augmenting rather than replacing architects' work. Jonah Hawk, an associate principal at ZGF Architects, has developed an internal AI toolkit, ZGF.ai, which includes tools for generating meeting notes, coding assistance, and image creation. Despite slow adoption rates, with only 6% of architects regularly using AI, the technology is seen as a means to enhance efficiency and client engagement. Experts emphasize the importance of architects understanding AI's capabilities and limitations, suggesting that those who leverage AI effectively may find new opportunities in the evolving landscape of the profession.